Maternal and perinatal outcomes among nulliparous adolescents in low‐ and middle‐income countries: a multi‐country study. Issue 13 (7th August 2013) - Ganchimeg, T; Mori, R; Ota, E; Koyanagi, A; Gilmour, S; Shibuya, K; Torloni, MR; Betran, AP; Seuc, A; Vogel, J; Souza, JP
Abstract : Objective: To investigate the risk of adverse pregnancy outcomes and caesarean section among adolescents in low‐ and middle‐income countries. Design: Secondary analysis using facility‐based cross‐sectional data from the World Health Organization (WHO) Global Survey on Maternal and Perinatal Health. Setting: Twenty‐three countries in Africa, Latin America, and Asia. Population: Women admitted for delivery in 363 health facilities during 2–3 months between 2004 and 2008. Methods: We constructed multilevel logistic regression models to estimate the effect of young maternal age on risks of adverse pregnancy outcomes. Main outcome measures: Risk of adverse pregnancy outcomes among young mothers. Results: A total of 78 646 nulliparous mothers aged ≤24 years and their singleton infants were included in the analysis. Compared with mothers aged 20–24 years, adolescents aged 16–19 years had a significantly lower risk of caesarean section (adjusted OR 0.75, 95% CI 0.71–0.79). When the analysis was restricted to caesarean section indicated for presumed cephalopelvic disproportion, the risk of caesarean section was significantly higher among mothers aged ≤15 years (aOR 1.27, 95% CI 1.07–1.49) than among those aged 20–24 years. Higher risks of low birthweight and preterm birth were found among adolescents aged 16–19 years (aOR 1.10, 95% CI 1.03–1.17; aOR 1.16, 95% CI 1.09–1.23, respectively) and ≤15 years (aOR 1.33, 95% CI 1.14–1.54; aOR 1.56, 95% CI 1.35–1.80, respectively). Conclusions: Adolescent girls experiencing pregnancy at a very young age (i.e. <16 years) have an increased risk of adverse pregnancy outcomes.